Identifikasi Pemahaman Konsep dan Self Efficacy Siswa pada Materi Struktur Atom dan Sistem Periodik Unsur - Nurwahyuni Nurwahyuni; Sri Hastuti Virgianti; Afadil Afadil (Universitas Tadulako, 2023)
Understanding the concept is a process in which students are able to understand the information obtained, both the definition, nature and description of a concept so that they are able to construct the concept. Self Efficacy is the ability of individuals to organize the actions needed for certain achievements. This study aims to (1) describe students' conceptual understanding of atomic structure material and the periodic system of elements. (2) describe student self-efficacy in atomic structure material and the periodic system of elements. The type of research used in this study was descriptive research with a quantitative approach. The instruments used in this study were three-tier questions and self-efficacy questionnaires. This research was conducted at SMAN 4 Palu in class X MIPA students. The results showed that students' understanding of concepts in atomic structure material and the periodic system of elements averaged the percentage of students who understood the concept of 34.35% classified as understanding the concept of the low category, students who did not understand the concept of 24.1% were in the low category while students who experienced a misconception of 41.35% in the sufficient category. The results of student self-efficacy research show that student self-efficacy is good because most are in the high category of 45 students (75%), the sufficient category is 15 students (25%).